Digital Communication Strategies in Promoting Sustainable Agriculture: Organic Products in Central Thailand - Somthawinpongsai, Chanyanan; Zhou, Fei; Wiwitkunkasem, Kasemrat; Chanwichian, Jeerabhan; Xing, Jia (Journal of Ecohumanism, 2024)
This study examines the determinants affecting the online purchasing decision-making process for organic agricultural products in community enterprises in central Thailand. The breadth of material encompasses: 1) the procurement decision-making process and 2) The concept and theory of online marketing, including content marketing. 3)The concept of the brand and 4)The study examined the concept of technology acceptance, specifically the Technology Acceptance Model (TAM), based on a sample of 400 individuals. The questionnaire employed a rating scale, utilizing the Likert method. We conducted a data analysis utilizing a structural equation model (SEM). This research's findings are advantageous for community enterprises in central Thailand in improving their online marketing strategies. The study demonstrated that the structural equation model for online content marketing, brand equity, and online marketing formats of organic agricultural products in community enterprises displayed R2 values of 0.68, 0.87, and 0.77, respectively. This suggests that the structural model may clarify the differences in online content marketing, brand equity, and online marketing techniques for organic agricultural products inside community enterprises. Corporations. The R2 values for the online marketing model of organic agricultural products in community businesses were 68%, 88%, and 77%, respectively. This shows that the model and the real-world data are strongly linked.